Happiness and Domestic Life The Influence of the Home on Subjective and Social Well-being - Russo, Maria Teresa; Argandoña, Antonio; Peatfield, Richard (Taylor & Francis, 2022)
This book uses a multidisciplinary approach to examine the relationship between the quality of domestic life and the home environment, in its material and relational dimension, with individual and social happiness, in the context of current changes. The theme of happiness and well-being is framed within two significant changes, themselves affected by the recent COVID-19 pandemic: the relationship between the individual's quality of life and engagement within the community, and the role of new technologies in everyday life. The authors highlight the relational nature of happiness and the centrality of the home environment in its promotion. Three dimensions of psychosocial well-being in the home are analysed: the personal one, consisting of a sense of stability, intimacy and sharing; the social one, which considers the domestic environment as a place for civic education and, in times of pandemic, the site of professional activity and the physical one, consisting of spaces, services and architectural styles. This book is ideal for readers who wish to cross disciplinary boundaries and explore the topic of domestic happiness in its different facets. The target audience is both professional researchers and advanced graduate and undergraduate students.